Pengaruh Pola Komunikasi Orang Tua Dalam Keluarga Terhadap Motivasi Belajar Peserta Didik Di MIS Pembangunan Al-Muhajirin Medan - Jihan Fadillah Lubis (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of parental communication in the family on students' learning motivation.This type of research is comparative causal. The population in this study were all students in class VI a and b at the Mis Pembangunan Al Muhajirin Medan denai T.A 2022-2023. The samples in this study were class VI A and VI B. Data were obtained by distributing questionnaires directly filled out by students. Data were analyzed descriptively and using the ANOVA technique. Is there an influence of parents' communication patterns on students' learning motivation at Mis Pembangunan Al Muhajirin Medan Denai? Is there a positive influence between parents' communication patterns on students' learning motivation at Mis Pembangunan Al Muhajirin Medan Denai? Is there a significant influence between parents' communication patterns on students' learning motivation at Mis Pembangunan Al Muhajirin Medan Denai? Based on the results of the data and discussion, it is obtained:There is an influence of parental communication in the family on the learning motivation of students at the Mis-Development Al-Muhajirin Medan Denai T.A 2022-2023. Through the results of the calculation of the T test that has been carried out, a value of 3.143 is greater than 2.005 with a significant level of 0.01 <0.05 and through the results of the calculation of the F test that has been carried out, a value of 7.097 is greater than 4.020 with a significant level of 0.01 <0.05. From the ???????????????????????????? test it is known that parental communication influences student learning motivation by 0.116 or 11.6%. The remaining 88.4% is influenced by other variables.